2015
DOI: 10.15537/smj.2015.8.11583
|View full text |Cite
|
Sign up to set email alerts
|

Independent risk factors for hypoxemia after surgery for acute aortic dissection

Abstract: Objectives:To determine risk factors associated with postoperative hypoxemia after surgery for acute type A aortic dissection.Methods:We retrospectively analyzed the clinical data of 192 patients with acute type A aortic dissection who underwent surgery in Qingdao Municipal Hospital, Medical College of Qingdao University, Qingdao, China between January 2007 and December 2013. Patients were divided into hypoxemia group (n=55) [arterial partial pressure of oxygen (PaO2)/fraction of inspired oxygen (FiO2) ≤200 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
4

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 26 publications
4
32
4
Order By: Relevance
“…None of the intraoperative variables were associated with hypoxemia in univariate analysis, but the CPB time was associated with hypoxemia in multivariable regression model. BMI was identified as an independent predictor of postoperative hypoxemia in the study, consistent with the study by Sheng and colleagues [ 14 ]. Actually, the association of obesity and hypoxemia is not limited to aortic surgery [ 18 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…None of the intraoperative variables were associated with hypoxemia in univariate analysis, but the CPB time was associated with hypoxemia in multivariable regression model. BMI was identified as an independent predictor of postoperative hypoxemia in the study, consistent with the study by Sheng and colleagues [ 14 ]. Actually, the association of obesity and hypoxemia is not limited to aortic surgery [ 18 ].…”
Section: Discussionsupporting
confidence: 91%
“…The incidence of hypoxemia was lower than those reported in the literature (20% vs. 30%) [ 4 , 14 ]. Different definitions of postoperative hypoxemia may explain its different incidences.…”
Section: Discussioncontrasting
confidence: 55%
“…Postoperative hypoxemia in TAAD patients was defined as a PaO 2 /FiO 2 ratio of 200 mmHg or lower (5,6). Postoperative refractory hypoxemia was defined as a persistent PaO 2 /FiO 2 ratio ≤100 mmHg despite conventional therapy within 6 hours of admission to the CSICU.…”
Section: Methodsmentioning
confidence: 99%
“…Hypoxemia is a frequent postoperative surgical complication in TAAD and is associated with increased mechanical ventilation duration, intensive care unit (ICU) stay, mortality and hospital costs (3). Although studies have raised questions about the association between TAAD and the risk factors for postoperative hypoxemia (4)(5)(6), the mechanism of hypoxemia in TAAD remains unclear but may…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study showed that a large number of AD patients may combine with acute lung injury (ALI), which severely affected the prognosis. Unfortunately, the exact mechanism of AAD complicated with ALI is still not well defined [2, 3]. Our previous study indicated that pulmonary microvascular endothelial barrier injury may present in patients with AAD, together with massive migration of macrophages and secretion of MMP-9, which finally induced ALI after interrupting the air-blood barrier [4].…”
Section: Introductionmentioning
confidence: 99%